Analisis Viktimologi Terhadap Hak-Hak Korban Kekerasan Berbasis Gender Online (KBGO) Melalui Penyebaran Konten Pornografi (Studi Putusan Nomor 616/Pid.Sus/2023/PN JKT.SEL) - Irene Olivia Siregar; Made Sugi Hartono; I Wayan Landrawan (Jurnal Ilmu Hukum Sui Generis, 2025)
This research aims to analyze victimology regarding the rights of victims of Online Gender- Based Violence (OGBV) through the distribution of pornographic content based on Decision Number 616/Pid.Sus/2023/PN JKT.SEL, focusing on (1) legal analysis of OGBV through the distribution of pornographic content on social media in Decision Number 616/Pid.Sus/2023/PN JKT.SEL, and (2) legal protection for victims of OGBV through the distribution of pornographic content on social media in Decision Number 616/Pid.Sus/2023/PN JKT.SEL. The main focus of this study is the distribution of pornographic content on social media without consent, involving digital sexual exploitation for economic gain. Using a normative juridical method with statutory, case, and conceptual approaches, this research examines the implementation of legal protection for OGBV victims. The findings indicate that although there is a legal framework governing victim protection, its implementation remains suboptimal, particularly in terms of comprehensive victim recovery. Data from SAFEnet Indonesia recorded a significant increase in OGBV cases in the first quarter of 2024, rising fourfold from 118 to 480 cases. This study emphasizes the importance of adopting a victim-centered justice approach within the criminal justice system and the need to strengthen the role of the Witness and Victim Protection Agency (LPSK) in ensuring victims' access to sustainable recovery services.